Political life of Erekle II and the Question of Georgian-Ossetian relationship - Sosiashvili, Giorgi (Actual Problems of Kartvelology, 2025)
The 18th century is distinguished by its special drama in the political life of Georgia. Surrounded by Muslim states - Iran and the Ottoman Empire - our country managed to maintain its existence at the cost of great hardship. The ruling circles of Kartli-Kakheti were in a constant search to find a strong ally for the weakened state and save the Georgian statehood from Muslim aggression. The unification of the Caucasus occupied a large place in the state vision of Erekle and Teimuraz, which primarily meant the establishment of close relations between the peoples living in the South and North Caucasus. In the fight against the external enemy, Erekle II often appealed to the peoples living in the Black Caucasus, including: Circassians, Kabardians, Ossetians.